Discours sur le corps et la sexualité des femmes : analyse de la réception médiatique du mouvement Femen - Tremblay, Stéphanie (Université du Québec à Montréal, 2022)
Le mouvement Femen est un groupe féministe international qui manifeste seins nus. Au Québec comme un peu partout dans le monde, les Femen attirent l’attention des médias. Le discours médiatique entourant ce mouvement constitue donc un objet d’étude intéressant afin d’explorer la question plus large du rapport au corps et à la sexualité des femmes. Dans le cadre de ce projet, une analyse critique de discours a été menée sur 214 textes issus de cinq groupes de quotidiens québécois francophones. Alors qu’on tend à penser que l’égalité entre les sexes est atteinte au Québec, le discours médiatique québécois entourant le mouvement Femen révèle que le corps, la nudité et la sexualité des femmes font l’objet d’un contrôle social en plus d’un regard patriarcal, colonialiste et hétéronormé. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Femen, agentivité sexuelle, slut-shaming, discours médiatique, féminisme, corps, nudité
Keywords: 2000 à aujourd'hui; 2010-2019; agentivité sexuelle; amériques; analyse de discours; approches et analyses; corps; discipline; hétérosexisme; intersectionnalité; militance; mémoires/thèses; nudité; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap